Aging, blade tenderization, and injection impacts tenderness of muscles from fed steers - Hutchinson, Stacy L.; Hunt, Melvin C.; Marston, T.T.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Enhancement of steer and heifer meat has become a common practice, especially for some large retailers in the United States, because it increases the weight of salable product and decreases variability in tenderness and juiciness. Enhancement also may reduce the aging period for some muscles. Muscles for this research were identified by National Cattlemen’s Beef Association (NCBA) as possible muscles in which value could be added with some type of postmortem tenderization treatment. If muscles are enhanced, aging may become less important, thus allowing more efficient and faster processing of those cuts. Therefore, the objective of this research was to determine the influence of aging period on tenderness of enhanced muscles from three intermediate-priced steaks.
Keywords: Beef; Cattle; Enhancement; Tenderness